Dual Role of Mechanisms Involved in Resistance to Predation by Protozoa and Virulence to Humans - Sun, Shuyang; Noorian, Parisa; McDougald, Diane (Frontiers in Microbiology, 2018)
Most opportunistic pathogens transit in the environment between hosts and the environment plays a significant role in the evolution of protective traits. The coincidental evolution hypothesis suggests that virulence factors arose as a response to other selective pressures rather for virulence per se. This idea is strongly supported by the elucidation of bacterial-protozoal interactions. In response to protozoan predation, bacteria have evolved various defensive mechanisms which may also function as virulence factors. In this review, we summarize the dual role of factors involved in both grazing resistance and human pathogenesis, and compare the traits using model intracellular and extracellular pathogens. Intracellular pathogens rely on active invasion, blocking of the phagosome and lysosome fusion and resistance to phagocytic digestion to successfully invade host cells. In contrast, extracellular pathogens utilize toxin secretion and biofilm formation to avoid internalization by phagocytes. The complexity and diversity of bacterial virulence factors whose evolution is driven by protozoan predation, highlights the importance of protozoa in evolution of opportunistic pathogens.